SEHAT DENGAN PUASA RAMADHAN PADA ANAK DI TK MELATI SIWALANPANJI BUDURAN SIDOARJO - Nurul Azizah; Rafhani Rosyidah, Paramitha; Amelia Kusumawardani (Universitas PGRI Adi Buana Surabaya, 2022)
Several studies state that fasting has many health benefits. Fasting in Ramadhan is obligatory for Muslims, therefore, fasting education for children from an early age is very important. Results of the pre-test survey, 78% of mothers (parents) didn’t know how to use the right method in training children to fast. This community service aimed at providing knowledge to mothers about training children to fast from an early age, this activity was attended by 30 mothers (parents) who were held at TK Melati Siwalanpanji Buduran Sidoarjo using a lecture method which contained recommendations for training children and implementing several methods to fast, as well as providing information about the privileges and benefits of fasting in children and followed by a question and answer session. The results of this activity showed that there was an increase, namely 90% of mothers showed good knowledge, this was supported by the response of mothers being enthusiastic and active in the activity by many questions. Conclusion: the mother was very enthusiastic about participating counselling activity on the fasting exercise method for children, and the entire series of activities had run fluent and received a good response from the school.